2016
DOI: 10.6028/nist.gcr.16-010
|View full text |Cite
|
Sign up to set email alerts
|

Survey and new directions for physics-based attack detection in control systems

Abstract: Monitoring the "physics" of control systems to detect attacks is a growing area of research. In its basic form a security monitor creates time-series models of sensor readings for an industrial control system and identifies anomalies in these measurements in order to identify potentially false control commands or false sensor readings. In this paper, we review previous work based on a unified taxonomy that allows us to identify limitations, unexplored challenges, and new solutions. In particular, we propose a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 63 publications
0
49
0
Order By: Relevance
“…Most of the previous work focuses on the unreliability of the sensor readings, while trusting actuators and controllers [51]. By contrast, we simulate integrity attacks on both sensors and actuators as depicted in Figure 2.…”
Section: Scenario I: the Tennessee-eastman Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the previous work focuses on the unreliability of the sensor readings, while trusting actuators and controllers [51]. By contrast, we simulate integrity attacks on both sensors and actuators as depicted in Figure 2.…”
Section: Scenario I: the Tennessee-eastman Processmentioning
confidence: 99%
“…There is an emerging trend in ICS intrusion detection research where researchers have shown growing interest in developing techniques that can detect such sophisticated attacks at the process level [8,9,22,28,31,35,46,50,51]. Although intruders may be able to hide in the IT network while figuring out their workings, the main driver of this trend is the observation that they can hardly hide their final goal, which is to cause an adverse effect on the physical process by maliciously manipulating sensor and control data [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…• Statistical protocol probes: they capture different statistical attributes and send them to the domain processor. These statistical attributes 7 We will use the term probes and agents interchangeably.…”
Section: Probesmentioning
confidence: 99%
“…Actual regulations, national standards, or guidelines are only suggestions and checklists for critical services providers. They do not supply a platform for detecting cyber threats and evaluating their consequences on the physical process allowing also reaction capabilities [7].…”
Section: Introductionmentioning
confidence: 99%